Cardiovascular disease and access to nutritious food for safety net patients. (June 2016) - Weintraub, Miranda Ritterman; Kelley, Elizabeth A.; Bozdech, Matthew; Yen, Irene H.
Abstract: Introduction: Cardiovascular disease (CVD) is the second leading cause of death in Alameda County, CA. Poor quality diet has been identified as an important contributor. Methods: This study assessed the association between the neighborhood modified retail food environment index (mRFEI), an indicator of patients' access to nutritious foods, and CVD diagnosis in Alameda County using data of patients seen at Highland Hospital between July 1, 2013 and June 30, 2014, (n = 39, 533). Patient addresses were linked to neighborhood level data (e.g. education level, median household income) and mRFEI. CVD diagnosis was based on ICD9 principal diagnosis codes given on initial hospital visit. Results: Logistic regressions modeled the CVD mRFEI association, considering covariates. CVD diagnosed patients were more likely to reside in neighborhoods with a lower ratio of healthy to unhealthy food options (adjusted OR = 0.97; 95% CI: 0.96 0.99). Conclusions: Our findings suggest nutritious food availability may play a role in the distribution of CVD.